Pollen loads used by Apis mellifera L. (Himenoptera: Apidae) in an area of subtropical forest in Northwestern Argentina - Mendez, Magali Veronica (2018)
In Northwest Argentina, Yungas subtropical forests are very important because of their huge vegetal diversity. Honeybees (A. mellifera) use these resources to feed and therefore as an ecosystemic service through beekeeping. The characterization of pollen flora of a region allows getting to know the food source and defining the importance of different plant species for colonies development and maintenance. The aim of the present study is to identify the pollen flora used by A. mellifera in the Yungas western area in Jujuy (Argentina) by means of their pollen loads characterization and to analyze the variations of two consecutive productive periods throughout spring and summer. To do this, 14 samples taken monthly were analyzed over the periods from September 2011 to March 2012 and September 2012 to March 2013. The samples were obtained from pollen traps at the entrances of the hives and were treated in the laboratory under conventional melisopalinology techniques with subsequent acetolysis. A total of 46 pollen types belonging to 25 botanical families were identified. The most important ones according to the family importance index are Euphorbiaceae (35.54), Fabaceae (26.27), Asteraceae (20.77), Vitaceae (16.14), Myrtaceae (9.13). Zanthoxylum, Sebastiania, Mimosa, Euphorbiaceae, Cactaceae, Parapiptadenia excelsa, Eupatorium, Cissus, Eucalyptus y Viguiera were identified as dominant resources. The variations of the breadth Index trophic niche show a floral resources selection for the area, where the use of native species stands out. The information produced in this study contributes to the knowledge of the resource offered by the forest and the species that are important for beekeeping production. Besides, it contributes to enhance the production and marketing of this product from its added value, allowing beekeepers a good management of hives.